Florence Nightingale's contribution to the ascendancy of nursing care: from the historical context to contemporary care (Research, Society and Development, 2020)
Nursing has its roots in empirical practices of women who cared for the sick of the family and for many years, it was carried out by priests, witches and religious. But they were difficult situations, as the activities still did not have a scientific basis, therefore, they were performed intuitively and under inadequate conditions. In the mid-19th century and under the influence of Florence Nightingale, the concepts underwent major changes, which in this way interfered and boosted the profession. It is a reflective study, with a historical perspective, whose idea emerged through the celebrations of Florence Nightingale's bicentenary, which aimed to describe Florence Nightingale's contributions from the perspective of Brazilian studies. The final sample consisted of only 23 references and subsequently, the content analysis outlined by Minayo was conducted, followed by the ordering and classification of data in three thematic categories incorporated throughout the text, which were: The historical context of Nursing; Florence Nightingale's contributions to modern nursing and the Nightingalean contribution to contemporary nursing. Florence was the founder of modern nursing, she stood out after her participation as a volunteer in the Crimean War, she reorganized care, promoted education, thereby breaking the prejudices of women in the army and transforming society's perception of the profession. It is concluded that the advances that Florence's theories brought are of great relevance, among them, it is worth highlighting the change in care, becoming broad and mainly making the human being an integral part of something beyond himself, part of an environment.